Community Influences on Attitudes Towards Unions. - Krahn, Harvey; Lowe, Graham (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1984)
This paper attempts to go beyond individual-level explanations of attitudes towards unions by exploring the impact of-community. It is argued that factors operating at the aggregate level of the community help shape local industrial relations. A review of industrial relations literature documents that community constitutes a latent but nonetheless important variable.